New cases that expand the genotypic and phenotypic spectrum of Congenital NAD Deficiency Disorder. Issue 7 (16th May 2021) - Szot, Justin O.; Slavotinek, Anne; Chong, Karen; Brandau, Oliver; Nezarati, Marjan; Cueto‐González, Anna M.; Patel, Millan S.; Devine, Walter P.; Rego, Shannon; Acyinena, Alicia P.; Shannon, Patrick; Myles‐Reid, Diane; et al.
Abstract: Nicotinamide adenine dinucleotide (NAD) is an essential coenzyme involved in over 400 cellular reactions. During embryogenesis, mammals synthesize NAD de novo from dietary l ‐ tryptophan via the kynurenine pathway. Biallelic, inactivating variants in three genes encoding enzymes of this biosynthesis pathway ( KYNU, HAAO, and NADSYN1 ) disrupt NAD synthesis and have been identified in patients with multiple malformations of the heart, kidney, vertebrae, and limbs; these patients have Congenital NAD Deficiency Disorder HAAO and four families with biallelic variants in KYNU . These patients present similarly with multiple malformations of the heart, kidney, vertebrae, and limbs, of variable severity. We show that each variant identified in these patients results in loss‐of‐function, revealed by a significant reduction in NAD levels via yeast genetic complementation assays. For the first time, missense mutations are identified as a cause of malformation and shown to disrupt enzyme function. These missense and frameshift variants cause moderate to severe NAD deficiency in yeast, analogous to insufficient synthesized NAD in patients. We hereby expand the genotypic and corresponding phenotypic spectrum of Congenital NAD Deficiency Disorder.